Information flow in general practice: investigating the processing of discharge summaries to improve patient safety - Spencer, Rachel A. (2019)
Discharge summaries are an essential tool for communicating patient information from secondary care to general practice on hospital discharge. Although there has been extensive research into their design and completion in secondary care very little is known about primary care perspectives on the processing of these documents. There is a need for greater understanding of the epidemiology of primary care patient safety in order to learn from current actions and processes and generate solutions to prevent future harm.